MODEL BIMBINGAN KLASIKAL DENGAN MENGGUNAKAN MEDIA CYBER COUNSELING (GOOGLE SITES) DALAM PERKEMBANGAN PEMILIHAN KARIER PESERTA DIDIK KELAS IX DI SMP NEGERI 5 SUNGAI LILIN KABUPATEN MUSI BANYUASIN - Risca Alvina Yuliani; Fifi Yasmi; Joni Adison (Berajah Journal, 2022)
The study in the background is that learners select undesirable career pathways and talents that discourage them from learning. The purpose of this study is to describe: 1. Describe the development of the student career choices. 2. Makes up a classification guide by using cyber-counseling (Google sites) to enhance the development of careers of participants by guidance teachers. The study was conducted using a quantitative method. The sample extraction technique USES samples used for the study to use adhesive samples with 58 learned packets divided into instruments used in the study is angkettes by data analiis techniques using percentages. The results of this study found: 1. Profile of the development of the study of the career learners are in the low category. 2. Model Design of the classical guidance service by using Cyber Counseling media (GOOGLE SITES) To improve the development of career election has been done by Master BK, then the researcher hopes that BK teachers can apply the classical guidance model using the Cyber Counseling Media in the development of the selection of Classical E-Classical Classes at SMP Negeri 5 Sungai Lilin. This research is recommended to Master BK to use Cyber Counseling Media (Google Sites) for classical guidance.